Measuring cultural diversity and its impact on innovation: Longitudinal evidence from Dutch firms - Ceren Ozgen; Peter Nijkamp; Jacques Poot (Institute for the Study of Labor (IZA), 2013)
To investigate econometrically whether cultural diversity of a firm's employees boosts innovation, we create a unique linked employer-employee dataset that combines data from two innovation surveys in The Netherlands with administrative and tax data. We calculate three distinct measures of diversity. We find that firms that employ fewer foreign workers are generally more innovative, but that diversity among a firm's foreign workers is positively associated with innovation activity. The positive impact of diversity on product or process innovations is greater among firms in knowledge-intensive sectors and in internationally-oriented sectors. The impact is robust to accounting for endogeneity of foreign employment.
Keywords: D22; F22; O31; 330; immigration; innovation; cultural diversity; knowledge spillovers; linked administrative and survey data; Diversity Management; Interkulturelle Kompetenz; Innovation; Migranten; Wissenstransfer; Niederlande